Implementation Strategies of Digital-Based Supervision to Improve The Quality of Education - Ekawaty, Agustina Endah; Satori, Djam'an; Triatna, Cepi; Herawan, Endang (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study investigates the implementation strategies of digital-based supervision to improve the quality of education at SMP Negeri 2 Bireuen, Aceh Province, using a qualitative research approach. Data were collected through in-depth interviews, observations, and document analysis related to the implementation of digital supervision in schools. The findings indicate that the application of digital-based supervision has positively impacted the quality of education at SMP Negeri 2 Bireuen. The use of technology in supervision has enabled education supervisors to gather data more quickly and accurately, facilitate more timely feedback to teachers, and enhance transparency and accountability in the evaluation process. This has encouraged teachers to innovate in their teaching approaches, contributing to improved student learning outcomes. The implications of this study suggest that the implementation of digital-based supervision can serve as an effective model for other schools in efforts to enhance education quality. However, adequate training and education for educators and supervisors are necessary to maximize the benefits of this supervisory technology. Additionally, attention must be paid to data security and privacy aspects to ensure safe and ethical use. Thus, the implementation strategies of digital-based supervision have the potential to serve as a tool for improving education quality in the future. Keywords: Educational Supervision, Digital Supervision, Education Quality